2016
DOI: 10.1007/s11099-015-0165-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water stress and rewatering on photosynthesis, root activity, and yield of cotton with drip irrigation under mulch

Abstract: Soil water deficit is a major limitation to agricultural productivity in arid regions. Leaf photosynthesis can quickly recover after rewatering and remain at a higher level for a longer period, thus increasing crop yield and water-use efficiency (WUE). We tested our hypothesis that leaf photosynthesis and root activity of water stressed cotton (Gossypium hirsutum L.) plants could quickly recover after rewatering at a certain growth stage and it should not influence a cotton yield but increase WUE. Treatments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(83 citation statements)
references
References 27 publications
8
74
0
1
Order By: Relevance
“…Asterisk represents significant difference in mz/rt peak between sensitive (G1) and tolerant (G2) varieties under the drought condition at a specific time point of samplingPereira, 2016;Cielniak, Filek, & Cielniak, 2006;J. Li et al, 2017;Luo, Zhang, & Zhang, 2016;Ullah, Sun, Yang, & Zhang, 2017;Zhou et al, 2017). Our results are aligned with other reported studies and demonstrated that the experimental condition separated the expression of these traits between the tolerant and sensitive varieties.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Asterisk represents significant difference in mz/rt peak between sensitive (G1) and tolerant (G2) varieties under the drought condition at a specific time point of samplingPereira, 2016;Cielniak, Filek, & Cielniak, 2006;J. Li et al, 2017;Luo, Zhang, & Zhang, 2016;Ullah, Sun, Yang, & Zhang, 2017;Zhou et al, 2017). Our results are aligned with other reported studies and demonstrated that the experimental condition separated the expression of these traits between the tolerant and sensitive varieties.…”
supporting
confidence: 90%
“…However, the sensitive variety showed greater F v / F m reduction than the tolerant variety. Some other studies also demonstrated a significant reduction of photosynthetic capacity and chlorophyll content due to stress condition (Basu, Ramegowda, Kumar, & Pereira, ; Cielniak, Filek, & Cielniak, ; J. Li et al, ; Luo, Zhang, & Zhang, ; Ullah, Sun, Yang, & Zhang, ; Zhou et al, ). Our results are aligned with other reported studies and demonstrated that the experimental condition separated the expression of these traits between the tolerant and sensitive varieties.…”
Section: Discussionmentioning
confidence: 89%
“…Research findings suggest that severe aridity can cause the dry weight of roots, root volume (Anbessa and Bejiga, 2002), and RLD of fine roots (Steinemann et al, 2015) to decrease, with a smaller average root diameter (Wang, 2007) and a decrease in root activity (Luo et al, 2016). In this paper, the excessive moisture stress caused by premature film removal resulted in significantly lower RLDs (Fig.…”
Section: Cotton Root Morphological Differences In Different Periods Imentioning
confidence: 61%
“…In fact, limitation of leaf growth is among the earliest visible impacts of water stress because leaves determine radiation interception and are the main photosynthetic organs [8]. Water deficit stress mostly reduced leaf water potential and growth and in turn the leaf areas in many species and leaf senescence could be observed under severe water stress [9,10,11]. In DOI : 10.9790/1813-0601010104 www.theijes.com Page 2 fact, development of optimal leaf area is important to photosynthesis and dry matter yield.…”
Section: Agro-morphological Plant Response To Drought Stressmentioning
confidence: 99%